Impact of subliminal messages and controversial product advertisement on online purchase intention with mediating role of offensiveness and self-regulation - Mahmood, Hamid
Where there is a concern of advertisement, it extends to various specialist areas. In agony, an advertisement was used for marketing and promotion purposes, but with the passage of time, marketing media re-established the advertising concept based upon manipulation with the usage of subliminal messages. Subliminal messages are designed in such a way that a common man is unable to understand what is being depicted. This research helps the general consumer to understand such advertisements. Bringing together cognition and marketing point of view, current research has paved a new way of imagination about marketing aligned with self-regulation. This research disentangles the notions of subliminal messages to check the implications of advertisements, in the shape of valuable results and the involvement of consumers' (students) in the marketing context. To examine the inducement of consumers motive via online buying impulsion and determine the significance and non-significance aspects, supportive or unsupportive consumers' involvement in controversial products. Further to analyze self-regulation stimulation in online buyers' motive of shopping. Also find out good or bad aspects of subliminal messages as per consumers' perceptions. Additionally, implement and test the suggested model for the awareness of consumers regarding controversial product advertisement and its exertion in current marketing trends. Current research was based on deductive approach taken from the positivist worldview. As per requirements of current research, the study is descriptive and explanatory in nature with a quantitative approach (deductive) highlighting the ideology, reaction and involvements of respondents. The respondents (students) for current research were selected using stratified random sampling technique and data were gathered from 600 respondents via self-administered questionnaire. Data was analyzed through Statistical Packages for Social Sciences (25.0) and Analysis of Moment Structures (24.0). Findings of current research guide the consumer's to understand such deranged marketing tactics. The results reveal substantial causal and effect relationship among the present study constructs. Current study findings pave the way for the identification of those aspects that positively contribute in the layman psyche toward online purchase intention. Hypothesis 1, 2, 3 and 4 supported the direct effect among constructs and mediation hypothesis of 5, 6, and 7 was also supported in which (5 and 6) have full and (7) ha partial mediation. Current research is different in nature regarding theoretical point of view because such con tructs have never been discussed together before. Present research led to the usage of theory of planned behavior entrenched with the current study model. Self-regulation model plays remedial role to stop unwilling participation that triggered via subliminal marketing strategies. The practical implications of self-regulation model in rational decision making of consumer's involvement, when pragmatic to the perspective of Pakistan are meaningful for new researchers and practitioners. This research would also be helpful for the Government to make regulation about current study issues.